2019
DOI: 10.1074/jbc.ra119.008218
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic structure of the full-length scaffolding protein NHERF1 influences signaling complex assembly

Abstract: The Na ؉ /H ؉ exchange regulatory cofactor 1 (NHERF1) protein modulates the assembly and intracellular trafficking of several transmembrane G protein-coupled receptors (GPCRs) and ion transport proteins with the membrane-cytoskeleton adapter protein ezrin. Here, we applied solution NMR and small-angle neutron scattering (SANS) to structurally characterize full-length NHERF1 and disease-associated variants that are implicated in impaired phosphate homeostasis. Using NMR, we mapped the modular architecture of NH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 64 publications
0
15
0
Order By: Relevance
“…Also, studies with EBP50 phosphomimicking mutants showed that ligand binding to PDZ2 blocks PDZ1 accessibility (Garbett et al ., 2010). This coordinated regulation of PDZ domain accessibility is most likely regulated by an allosteric mechanism in which ligand binding induces a long range conformational change of EBP50 (Bhattacharya et al , 2010; Bhattacharya et al , 2019; Li et al ., 2009). An interaction of both PDZ domains with the same ligand has also been found for the interaction of EBP50 with the cystic fibrosis transmembrane conductance regulator (CFTR) as well as for the interaction of E3KARP with PTEN (Short et al , 1998; Takahashi et al , 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Also, studies with EBP50 phosphomimicking mutants showed that ligand binding to PDZ2 blocks PDZ1 accessibility (Garbett et al ., 2010). This coordinated regulation of PDZ domain accessibility is most likely regulated by an allosteric mechanism in which ligand binding induces a long range conformational change of EBP50 (Bhattacharya et al , 2010; Bhattacharya et al , 2019; Li et al ., 2009). An interaction of both PDZ domains with the same ligand has also been found for the interaction of EBP50 with the cystic fibrosis transmembrane conductance regulator (CFTR) as well as for the interaction of E3KARP with PTEN (Short et al , 1998; Takahashi et al , 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, structural analysis revealed significant differences in the NHERF1 protein harboring these mutants, compared to the wild-type protein. 8 Further functional analysis of these variants, particularly in sensory neurons, might be informative.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of this with the use of higher resolution techniques on the well-folded domains can offer insights into both the local and global effects of mutations or conformational changes. A recent study of the NHERF1 scaffold protein combined NMR for domain level analysis with SANS to extrapolate the effects of single amino acid substitutions on global dynamics [48]. Three disease variants from individual amino acid substitutions were found to alter the global conformation of the protein and significantly alter the local PDZ domain structure [48].…”
Section: How Do the Sam Domains Exist In The Context Of Their Immedia...mentioning
confidence: 99%